Nursing assistance for child victims of burn: integrative review (Research, Society and Development, 2022)
Children represent the highest percentage of burn victims, being the second most common cause of accidents in childhood, leading to high morbidity and major sequelae. Objectives: To analyze the nursing care provided to children with burns. Methods: The present study is an integrative literature review study. Used as a database: LILACS, PUBMED, SciELO, accessed by the Virtual Health Library (VHL) and ScienceDirect in Portuguese, English and Spanish. The following descriptors were used: "Nursing Care", "Child" and "Burn" from the PICo strategy. Articles that presented the theme for adults/elderly patients, review studies, book chapters, thesis and Dissertations. We obtained 9 selected articles where the high occurrence of burns involving the pediatric population was evidenced, patenting scalding as the most frequent cause of these accidents. The initial approach and treatment of the burned child is of great importance, since such actions benefit healing, reduce mortality and the risk of complications. Considering the selected studies, the importance of nursing care and its interventions with the pediatric burn victim was highlighted. It is understood the need for more updated studies aimed at child population and the most effective measures that can be carried out by the nursing team, aiming at the benefit and patient recovery.